Manual of fish health : everything you need to know about aquarium fish, their environment and disease prevention - Andrews, Chris , 1953-; Carrington, Neville; Exell, Adrian (Firefly Books, 2010)
This book is a comprehensive guide to keeping fish healthy for the serious hobbyist. A healthy environment is crucial for any aquarium. Fish need more than a tank of water and a daily sprinkle of food to stay healthy, and the fish-keeper is regularly challenged to understand irregularities that can cause trouble. Manual of Fish Health is a fully illustrated and highly informative reference that concentrates on: Maintaining a healthy aquatic environment; Recognizing and coping with pests, diseases, parasites and bacteria; Balancing water chemistry so the fish's environment is always healthy. The book also includes an A to Z directory of common pests and diseases and a practical guide to their control and treatments. The expert authors explore the vital aspects of health care for all types of fish, including freshwater and saltwater, tropical and temperate, and pond and aquarium. The clear and concise text is abundantly illustrated with underwater photography, charts and diagrams. - Publisher